(untitled) (Research, Society and Development, 2023)
Introduction: Treatment-Resistant Depression (TRD) does not have an absolute consensus on its definition, but can be understood as a severe depressive condition with an unsatisfactory response to two antidepressants from two different classes. Ketamine is a dissociative anesthetic that has an antagonistic action on glutamate/aspartate receptors, therefore, it acts in the pathophysiological condition of depression. Objective: The present study seeks to examine the particularities of the use of ketamines in people who do not improve with conventional treatments for depression. Materials and Methods: This is an integrative literature review about the role of using ketamines in patients refractory to treatment. The PICO strategy was used to prepare the guiding question. Furthermore, the descriptors “Refractory depression” were crossed; “Ketamines”; “Management”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: Refractory depression is serious without a clear definition. Both ketamine and electroconvulsive therapy (ECT) are considered satisfactory treatments and do not demonstrate differences in reducing suicidal ideation in these patients. Conclusion: This review highlights that for better management of ESRD it is necessary to formalize the therapeutic approach protocol for this disorder. Furthermore, it reveals that ketamines present superior results to other pharmacological measures and are very similar to ECT, but require follow-up due to the high rate of recurrence.